2013
DOI: 10.1038/ni.2772
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the kinase Csk in thymocytes reveals a requirement for actin remodeling in the initiation of full TCR signaling

Abstract: T cell receptor (TCR) signaling is initiated by Src-family kinases (SFKs). To understand how C-terminal Src kinase (Csk), the negative regulator of SFKs, controls the basal state and the initiation of TCR signaling, we generated mice expressing a PP1-analog inhibitor-sensitive Csk variant (CskAS). Inhibition of CskAS in thymocytes, without TCR engagement, induced potent SFK activation and proximal TCR signaling up to phospholipase C-γ1 (PLC-γ1). Surprisingly, increases in inositol phosphates (InsP), intracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(111 citation statements)
references
References 54 publications
9
98
0
Order By: Relevance
“…With the exception of PKA and CSK, the expression of these kinases is predominantly restricted to immune cells, suggesting selective roles in immune modulation. Accordingly, genetically engineered mouse models enabling the abrogation of PKA, CSK, MAP4K1, or DGKξ functions exhibit hallmarks of excessive immune activation and/or TCR hypersensitivity (128,(130)(131)(132) -/-mice, the role of these kinases in tumor immune surveillance has already been established, confirming the viability of these approaches for restoring antitumor immunity (131,133). In contrast, ubiquitous expression and pleiotropic functions of CSK and PKA may limit the viability of these targets in this context.…”
Section: Future Directionsmentioning
confidence: 87%
“…With the exception of PKA and CSK, the expression of these kinases is predominantly restricted to immune cells, suggesting selective roles in immune modulation. Accordingly, genetically engineered mouse models enabling the abrogation of PKA, CSK, MAP4K1, or DGKξ functions exhibit hallmarks of excessive immune activation and/or TCR hypersensitivity (128,(130)(131)(132) -/-mice, the role of these kinases in tumor immune surveillance has already been established, confirming the viability of these approaches for restoring antitumor immunity (131,133). In contrast, ubiquitous expression and pleiotropic functions of CSK and PKA may limit the viability of these targets in this context.…”
Section: Future Directionsmentioning
confidence: 87%
“…Prominent among these pathways are those that involve remodeling the actin cytoskeleton and the PI3K pathway. As a preliminary effort to explore this dataset, we focused on the actin cytoskeleton because our recent studies (32) and those of others (29) suggested an important role for CD28 in regulating the actin cytoskeleton. The genetic study of Liang et al (29), which identified an important role of Rlptr, led us to focus on CapZIP.…”
Section: Discussionmentioning
confidence: 99%
“…In the ground state, the levels of active LCK are set to a point ensuring that maximal CD3 ITAM and ZAP-70 phosphorylation only occurs upon engagement of the TCR with agonist pMHC ligands. Consistent with the existence of such basal PTK-PTPase balance, its alteration in favor of PTK via genetic or pharmacological interventions can increase TCR sensitivity (9) and even trigger T cell activation, irrespective of TCR-pMHC engagement (5,10).…”
Section: T He Recognition Of Peptide-mhc (Pmhc) Ligands By T Cells Anmentioning
confidence: 82%
“…For instance, in response to very weak interactions with self-pMHC, the TCR signaling pathway found in naive T cells, rather than being silent, delivers low-intensity signals that imprint on naive T cells a heightened reactivity to foreign pMHC (2). A network of PTKs, protein tyrosine phosphatases (PTPases), and transmembrane adaptors dynamically control the activity of LCK in the ground state (3)(4)(5)(6)(7)(8). In the ground state, the levels of active LCK are set to a point ensuring that maximal CD3 ITAM and ZAP-70 phosphorylation only occurs upon engagement of the TCR with agonist pMHC ligands.…”
Section: T He Recognition Of Peptide-mhc (Pmhc) Ligands By T Cells Anmentioning
confidence: 99%